The importance of language proficiency among business studies students - Kum Yoke, Soo; Zainon, Saunah; Bai Rajendran, Cecilia; Nur Hidayah Kamaludin, Puteri; Hassanuzin, Salsabilla; Mohd Yusof, Suhaili (International Journal of Engineering and Technology, 2018)
Language proficiency among business studies students are essential to their ability to gain knowledge as well as to communicate their thoughts and ideas to others. However, it has been found that students in the field of business put less effort and interest in improving their languge proficiency simply because they place greater importance on their core courses. The aim of this study is therefore to investigate the reasons behind business studentsâ€™ lack of interest and to introduce innovative learning methods to improve their language proficiency. The government in its plan and policy for higher learning institutions has stipulated that language proficiency through the Malaysian University Entrance Test (MUET) and the English Exit Test (EET) is compulsory for all students in order to gain entrance and to graduate. Thus, it is vital that students place importance in the language courses at the university. By means of an experimental method, data was collected through treatment of a control group and an experimental group on language learning. After the treatment was implemented, a short grammar test was given to the students. A structured interview was then carried out to determine studentsâ€™ interest in the language proficiency classes. The study found that language proficiency could be improved with new methods of input by means of digital story telling. Students showed interest when learning language rules were disseminated through innovative digital story telling. Further, it was identified that they were not sure of the basic grammatical elements at first but were more confident after the experiment. However, the study was limited to only a small group of business students and therefore for future research can be expanded to a greater group of students from different field of studies.Â